2009
DOI: 10.2174/138955709788452630
|View full text |Cite
|
Sign up to set email alerts
|

D-Serine Regulation: A Possible Therapeutic Approach for Central Nervous Diseases and Chronic Pain

Abstract: D-Serine, an endogenous modulator of NMDA receptors has been shown to play a vital role in many neuropsychiatric functions such as learning, memory, nociception and implicated in pathological conditions like schizophrenia and Alzheimer's disease. We propose possible therapeutic approaches for some CNS diseases and chronic pain, targeting the D-serine levels by manipulating its uptake, biosynthesis and metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…A similar reduction in intracellular D-Ser concentration was observed after incubation with gabapentin and ( S )-pregabalin, which reduce intracellular Ca 2+ concentrations via inhibition of the α 2 -δ subunit of voltage-gated calcium channels [24]. Based upon these observations and the recent report identifying a relationship between reduced D-Ser concentrations and attenuated NMDA receptor activity in rat and mouse models [22], it is reasonable to assume that a ( 2S,6S )-HNK-associated reduction in D-Ser production should also result in reduced NMDA receptor activation and associated neurotoxicity, synaptic death and depression.…”
supporting
confidence: 53%
See 2 more Smart Citations
“…A similar reduction in intracellular D-Ser concentration was observed after incubation with gabapentin and ( S )-pregabalin, which reduce intracellular Ca 2+ concentrations via inhibition of the α 2 -δ subunit of voltage-gated calcium channels [24]. Based upon these observations and the recent report identifying a relationship between reduced D-Ser concentrations and attenuated NMDA receptor activity in rat and mouse models [22], it is reasonable to assume that a ( 2S,6S )-HNK-associated reduction in D-Ser production should also result in reduced NMDA receptor activation and associated neurotoxicity, synaptic death and depression.…”
supporting
confidence: 53%
“…Variations in endogenous D-Ser levels have been correlated with a number of CNS diseases and pathological states, as increased levels of D-Ser in the CNS have been linked to amyotrophic lateral sclerosis and Alzheimer’s disease while decreases in CNS concentrations of D-Ser have been associated with schizophrenia [18]. Thus, modulation of SR activity is an area of pharmacological and clinical interest [18,22]. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because d-Ser also acts as an agonist of N-methyl-d-aspartate (NMDA) receptormediated neurotransmission in the brain, it may be useful as innovative pharmacologic strategy in schizophrenia and pain [205]. A strain of protozoa (Drosophila melanogaster) has developed a transport mechanisms with adaptive specialization in the absorption and brain functions of d-Ser and other DAA that may be involved in neuronal functions [206].…”
Section: 4mentioning
confidence: 99%
“…Thus, several studies have found an association between the activity of serine racemase and schizophrenia (Labrie et al 2009), Alzheimer's disease (Hashimoto et al 2004), and age-related memory loss (Mothet et al 2006). D-Ser may also be useful as an innovative pharmacologic strategy in the treatment of these diseases (Coyle et al 2010;Sethuraman et al 2009), as well as for ameliorating pain (Muth-Selbach et al 2004) and treating anxiety disorders (Matsuda et al 2010). Further research is needed to clarify the consequences of D-Ser exposure on pathways implicated in neuronal functions and neurodegenerative disorders (Davidson et al 2009).…”
Section: D-serinementioning
confidence: 99%